KYRGYZ PHILOSOPHY IN THE UPBRINGING OF CHILDREN (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article proves that the Kyrgyz people have been paying special attention to the upbringing of children since time immemorial, a child is a wealth of a domestic type, the joy of parents, and procreation. It is said that the philosophy of education of the Kyrgyz people is not just a council or a set of rules, it is based on spiritual values, traditions, and the instructions of their ancestors. Kyrgyz philosophy in the upbringing of children includes national characteristics and is aimed at educating the younger generation of such qualities as humanity, respect for elders, dedication to service to the younger and parents, hard work.
Keywords: philosophy of education, basic people, being human, the spirit of nature, personality, spiritual health, spiritual purity, new generation, respect.